Mashru Tarmim Masjid wa-Madrasat al-Sultan al-Ghuri : athar raqm, 189, 909 H-1503 M - Gaballa, G. A. ([Wizārat al-Thaqāfah, al-Majlis al-Aʻlá lil-Āthār], 2000)
al-Ṣulṭān al-Ghūrī's mosque and school; Egypt; documentation; restoration; conservation; development; projects; pictorial work.